Smart and Secure? Millennials on Mobile Devices - Peter Holicza; Esmeralda Kadëna (Interdisciplinary Description of Complex Systems, 2018)
Millennials, members of the Generation Y are constantly connected to their social circles online, they are the founders of the social media movement. These young consumers count as the largest segment of smartphone owners in most regions of the world. In fact, smartphones have become one of the most important possessions of this highly technology savvy generation. However, the advanced and widespread use of mobile devices often does not meet with the required security consciousness. People who have grown up with internet, are more likely to share personal and sensitive corporate information online by using the same device for both work and private applications, accessing free Wi-Fi networks or borrowing other devices without the appropriate protection. This work examines the crucial smartphone security risks that users face with the new technology. It aims to investigate how their practices and behaviours can pose security risks on their smartphones usage. Security practices and awareness can be improved by increasing users’ knowledge. To accomplish this, education on technology is needed.